The students’ perspectives of platforms used in virtual learning environment: a survey study in COVID-19 pandemic - H Haryati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
COVID-19 has been the pandemic in Indonesia since March 2020. Drastically, it impacts on educational segment; therefore, the platforms of digital tools are able to be the best alternative way to overwhelm this issue and to strengthen the material delivery conducted by educational institution including universities. They can be beneficial tools in COVID-19 pandemic condition as teachers’ assistance. Due to these issues, this study was conducted to determine students’ perspective on the implementation of platforms in virtual learning environment during Covid-19 pandemic. This study involved 105 participants of the sixth semester students of English department of Universitas Pamulang. To obtain the data, the writer distributed a survey consisting 3 major questions (the platform reference, the advantages and the challenges); the students handed the reflective notes in to all questions related to the implementation of virtual learning in COVID-19 pandemic situation. The findings revealed that the students prefer having screen recording in learning activity (38.10%), Google Meeting (28.57%), Kahoot (19.04%), and Ed Puzzle (14.29%). Furthermore, the advantages of the platforms are time flexibility, effective platforms, less quota, interaction, fun application, the mastery of grammar; however, the challenges are monotonous activity, the students’ boredom, difficult to create an account, poor responses, poor internet connection and inequivalent schedule.